Direct nano-imaging of light-matter interactions in nanoscale excitonic emitters - Kiyoung Jo; Emanuele Marino; Jason Lynch; Zhiqiao Jiang; Natalie Gogotsi; Thomas P. Darlington; Mohammad Soroush; P. James Schuck; Nicholas J. Borys; Christopher B. Murray; Deep Jariwala (Nature Communications, 2023)
Abstract Strong light-matter interactions in localized nano-emitters placed near metallic mirrors have been widely reported via spectroscopic studies in the optical far-field. Here, we report a near-field nano-spectroscopic study of localized nanoscale emitters on a flat Au substrate. Using quasi 2-dimensional CdSe/CdxZn1-xS nanoplatelets, we observe directional propagation on the Au substrate of surface plasmon polaritons launched from the excitons of the nanoplatelets as wave-like fringe patterns in the near-field photoluminescence maps. These fringe patterns were confirmed via extensive electromagnetic wave simulations to be standing-waves formed between the tip and the edge-up assembled nano-emitters on the substrate plane. We further report that both light confinement and in-plane emission can be engineered by tuning the surrounding dielectric environment of the nanoplatelets. Our results lead to renewed understanding of in-plane, near-field electromagnetic signal transduction from the localized nano-emitters with profound implications in nano and quantum photonics as well as resonant optoelectronics.